Cobalt‐Catalyzed Alkyne Hydrosilylation and Sequential Vinylsilane Hydroboration with Markovnikov Selectivity. (1st August 2016) - Zuo, Ziqing; Yang, Ji; Huang, Zheng
Abstract: A pyridinebis(oxazoline) cobalt complex is a very efficient precatalyst for the hydrosilylation of terminal alkynes with Ph2 SiH2, providing α‐vinylsilanes with high (Markovnikov) regioselectivity and broad functional‐group tolerance. The vinylsilane products can be further converted into geminal borosilanes through Markovnikov hydroboration with pinacolborane and a bis(imino)pyridine cobalt catalyst.